Efficacy and Safety of Bupivacaine (Local Anaesthetic) Infiltration at Wound Site for Post-Operative Pain Relief in Cases Undergoing Elective Abdominal Surgery - a Randomised control trial - Hombal, Prashant; Gudadappanavar, Anupama; Javali, Shivalingappa (Pain medicine, 2024)
Objectives: The efficacy and safety of Bupivacaine infiltration at the wound site were studied for postoperative pain relief in patients undergoing elective abdominal surgery. Methods and Materials: A randomized clinical trial conducted in an institution of medical education and a tertiary care centre. A total of 90 patients who were scheduled for elective abdominal surgery were randomly assigned to one of two groups. Bupivacaine infiltration was given to Group T, while sterile water was given to Group C at the incision site just before closure of the wound. The pain intensity was measured using the Visual Analogue Score (VAS) at different time intervals after surgery. The requirements for rescue analgesic, pain VAS, patient satisfaction score, and side effects were recorded over the course of 24 hours following surgery. The data was statistically analysed and expressed as a mean +/- standard deviation. The data was analysed using the Chi-square test, Mann-Whitney U test, and Wilcoxon Test of matched pairs. *P < 0.05 is considered statistically significant. Results: The difference in VAS score after 2 hrs, 4 hrs, 8 hrs, and 24 hrs was found to be significantly higher in the control group as compared to the experimental group. At the end of 24 hrs, the mean score in the control group was 3.02 ± 0.66, which is higher as compared to the experimental group, which was 2.33± 0.67 (p<0.05). Conclusion: Infiltration of Bupivacaine at the incision site was extremely effective for post-operative pain control with maximum patient satisfaction. This study may provide new evidence to formulate guidelines for optimum pain management in the postoperative setting for the benefit of patients with a reduced need for analgesics.